The Use of the Question Card Playing Method Mathematics for Class VI Students of SD Negeri 22 Kepahiang - Husin Husin (Perkumpulan Dosen Muda (PDM) Bengkulu, 2020)
Classroom action research aims descriptively to determine the effect of the question card playing method on improving the ability to work on story problems in class VI mathematics at SD Negeri 22 Kepahiang in 2020/2021. The hypothesis in this study is